(untitled) (UNED Research Journal, 2024)
Introduction: Modern agriculture seeks to improve sustainability and reduce environmental impact, while meeting the nutritional needs of current and future generations. A promising strategy is the use of microbial biostimulants to increase crop yields and decrease dependence on agrochemicals and fertilizers. Among these biostimulants, those that use beneficial microorganisms such as plant growth-promoting bacteria stand out. We focused this study on isolating and identifying lactic acid bacteria present in artisanal bioles, and characterizing them by their ability to produce indolic compounds. The findings suggest that some lactic acid bacteria present in the two bioles samples can act as producers of indole compounds, such as 3-indoleacetic acid, which makes them a promising alternative for more sustainable and environmentally friendly agricultural practices. Objective: Isolate and identify lactic acid bacteria present in two samples of artisanal biole, and characterize them by their growth and their ability to produce indolic compounds. Methods: We use molecular techniques such as 16S rRNA gene analysis and multilocus typing sequencing analysis to identify strains of lactic acid bacteria present in artisanal biole. Subsequently, we characterized the isolated strains using growth kinetics and colorimetric tests for the detection of indolic compounds, and the quantification of said compounds using high-efficiency liquid chromatography (HPLC). Results: We identified three different genera of lactic acid bacteria species which were Lacticaseibacillus paracasei, Lactiplantibacillus sp., and Lacticaseibacillus pantheris. Lactiplantibacillus sp. stood out for their ability to produce 3-indoleacetic acid. (M2) and Lacticaseibacillus paracasei (M4) with a concentration of 16,75 µg/mL and 4,57 µg/mL, respectively. Conclusion: Our results suggest that some lactic acid bacteria present in artisanal bioles can act as producers of indolic compounds such as 3-indoleacetic acid, which makes them a promising alternative for more sustainable and environmentally friendly agricultural practices.